Modeling marital conflict based on self differentiation and familism through the mediation of intimacy and emotional maturity in the family - Mirzaie Kondori, Fataneh; Abdi Zarin, Sohrab; Aghayousefi, Alireza (Applied Family Therapy Journal (AFTJ), 2022)
Aim: The aim of this study was to model marital conflict based on self-differentiation and familism orientation with the mediating role of intimacy and emotional maturity in the family. Methods: The present study is an applied research in terms of purpose and in terms of method is correlational research and structural equation modeling. In this study, the population includes all couples living in Tehran. And available Sampling method was used. 1107 people answered the questionnaire and 295 couples (590 couples) were selected as the research sample. An online version was sent to the people who announced their readiness to cooperate and the necessary explanations in this regard were provided. Data collection tools included: Marital Conflict Questionnaire (MCQ), Self-Differentiation Questionnaire (DSI), Familism scale, Emotional Maturity Scale. In the inferential statistics section, path analysis and structural equation modeling were used to analyze the data and test the hypothesis, and SPSS and smart-pls software were used. Results: Data analysis showed this model has a good fit and between self-differentiation and marital conflict; Between self-differentiation and emotional maturity; Between familyism and emotional maturity; Between familyism and marital conflict; Between intimacy and marital conflict there is a significant relationship between emotional maturity and marital conflict.The results also showed that the mediating role of emotional maturity in the model was significant but the mediating role of intimacy in the model was not significant. Conclusion: As a result, these variables can be considered in medical and counseling centers in resolving marital conflict.